Herbivory on the pedunculate oak along an urbanization gradient in Europe: Effects of impervious surface, local tree cover, and insect feeding guild. Issue 3 (14th March 2022) - Valdés‐Correcher, Elena; Popova, Anna; Galmán, Andrea; Prinzing, Andreas; Selikhovkin, Andrey V.; Howe, Andy G.; Mrazova, Anna; Dulaurent, Anne‐Maïmiti; Hampe, Arndt; Tack, Ayco Jerome Michel; Bouget, Christophe; Lupaștean, Daniela; et al.
Abstract: Urbanization is an important driver of the diversity and abundance of tree‐associated insect herbivores, but its consequences for insect herbivory are poorly understood. A likely source of variability among studies is the insufficient consideration of intra‐urban variability in forest cover. With the help of citizen scientists, we investigated the independent and interactive effects of local canopy cover and percentage of impervious surface on insect herbivory in the pedunculate oak ( Quercus robur L.) throughout most of its geographic range in Europe. We found that the damage caused by chewing insect herbivores as well as the incidence of leaf‐mining and gall‐inducing herbivores consistently decreased with increasing impervious surface around focal oaks. Herbivory by chewing herbivores increased with increasing forest cover, regardless of impervious surface. In contrast, an increase in local canopy cover buffered the negative effect of impervious surface on leaf miners and strengthened its effect on gall inducers. These results show that—just like in non‐urban areas—plant–herbivore interactions in cities are structured by a complex set of interacting factors. This highlights that local habitat characteristics within cities have the potential to attenuate or modify the effect of impervious surfaces on biotic interactions. Abstract : We investigated the independent and interactive effect of impervious surface and local canopy cover on insect herbivory on the pedunculate oak throughout most of its distribution in Europe through a citizen science project. We found that local canopy cover within cities has the capacity to mitigate the effect of impervious surface on biotic interactions, as it influences the effect of impervious surface on herbivores differently. Therefore, this study supports the importance of maintaining trees in urban areas as it may consequently contribute to the preservation of biodiversity of insect herbivores in urban areas.